MEMUPUK KEMAMPUAN BERMATEMATIKA SEJAK DINI MELALUI AKTIVITAS BERMAIN - I Komang Sesara Ariyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Mathematics for early childhood is actually a fun activity. Early childhood needs to play activities using concrete objects and move towards more abstract things gradually in order to understand mathematics. Although mathematics for early childhood is more about numbers, early childhood also needs to understand other concepts such as geometry and measurement. These math concepts are learned by children through play activities. These activities encourage children's logical thinking activities such as matching, comparing, classifying, differentiating, measuring, sorting, and checking for certain patterns. Therefore, early childhood has been doing mathematics since childhood. This paper will discuss (1) how mathematical abilities are for early childhood, (2) early childhood math play activities, and (3) what kinds of games can be applied in facilitating children's learning about early math concepts. Most math games for children use concrete and semi-abstract media such as pictures. The math games offered in this paper are only a few examples that have been done by kindergarten teachers or researchers in Indonesia.